Experimental Study on Fatigue Behaviour of BFRP-Concrete Bond Interfaces under Bending Load - Jianhe Xie; Jianglin Li; Zhongyu Lu; Huan Zhang (Shock and Vibration)
Basalt fiber reinforced polymer (BFRP) composites are increasingly being used to retrofit concrete structures by external bonding. For such strengthened members, the BFRP-concrete interface plays the crucial role of transferring stresses. This study aims to investigate the fatigue behaviour of the interface under bending load. A series of tests were conducted on BFRP-concrete bonded joint, including static, fatigue, and postfatigue loading. The fatigue failure modes, the development of deflection, the evolution of BFRP strains, and the propagation of interfacial cracks were analysed. In addition, the debonding-induced fatigue life of BFRP-concrete bonded joints was studied. Finally, a new model of fatigue life was proposed by defining the effective fatigue bond stress. The results showed that the fatigue experience has a significant effect on the BFRP strength especially near the root of concrete transverse crack and on the bond performance of the adhesive near the interface crack tip. There are two main fatigue failure modes: BFRP rupture and BFRP debonding. The fatigue damage development of the bond interface has three stages: rapid, stable, and unstable growth. The proposed model for the debonding-induced fatigue life is more conservative for the BFRP-concrete bonded joints under pure shear load than for those under bending load.